Development of the SIMPAUD Model in Early Childhood Education (PAUD) Management - Rahmatullah, Alfian; Yuliantina, Irma (STAI Miftahul Ula Nganjuk, 2025)
This study aims to develop the digitalization of educational management in Early Childhood Education (PAUD) through the implementation of the SIMPAUD Merdeka system, using the ADDIE development model. The research method employed is Research and Development (R&D), with both qualitative and quantitative data analysis techniques. The population of this study consists of teachers and staff at TK Rausan Fikri. In the Analysis phase, needs were identified based on relevant educational management theories. The Design phase focused on the development of the system architecture and the creation of a user-friendly and intuitive interface. In the Development phase, coding, system integration, and the implementation of relevant data structures were carried out. The system was implemented at TK Rausan Fikri, accompanied by teacher training to ensure optimal system usage. The effectiveness of the system was evaluated using the USE questionnaire (Usefulness, Satisfaction, and Ease of Use), which indicated that SIMPAUD Merdeka effectively meets user needs. The evaluation results also confirmed that the system is suitable for implementation in PAUD educational units.